Endoscopic nasal dacryocystorhinostomy: Results of Hospital Professor Doutor Fernando Fonseca - Barbosa, Leonel (2015)
Objective: analyze the results of a district hospital’s experience in endoscopic dacryocystorhinostomy and state the current role of this technique in the treatment of distal nasolacrimal pathway obstruction.Methods: the clinical records of 67 consecutive endoscopic dacryocystorhinostomies performed in Hospital Professor Doutor Fernando Fonseca between January 1997 and December 2012 were reviewed. The clinical presentation, level of stenosis detected in the dacryocystography, intraoperative and postoperative complications and functional and anatomical results were analyzed.Results: Of the 51 patients, 12 were male and 34 female, with an age-average of 57 years. Epyphora was the main symptom. With the exception of two cases, all surgeries were performed with powered tools. Endoscopic dacryocystorhinostomy success rate was 78,1%.Conclusions: Endoscopic dacryocystorhinostomy is a simple, safe and effective technique for the treatment of distal obstructions of the nasolacrimal pathway.